Implementation of AHP and Black Box Testing to the Development of an Information System for Assessing the Feasibility of BUMDES Submissions - Hari Toha Hidayat; Husaini Husaini; Nanang Prihatin; Radhiyatammardhiyyah Radhiyatammardhiyyah (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2022)
The existence of institutional village enterprises (BUMDES) has never been adequately monitored in terms of the growth of village-owned businesses in each village. According to the data, there are 17 BUMDES in the Muara District that have been inactive for the most part. Due to the difficulty of monitoring the progress of BUMDES, a significant number of them have become stalled or even inactive. In addition, many BUMDES managers are frequently unprepared to operate the newly opened business. Readiness in terms of the quality of human resources also affects the formation of BUMDES. Consequently, the objective of this study is to facilitate the monitoring of business developments carried out by BUMDES actors in their respective villages, thereby facilitating the feasibility assessment of BUMDES. Aside from that, the purpose of this study is to determine the viability of applying for BUMDES as one of the requirements for obtaining a recommendation from the village head for submission to the Village Ministry. The feasibility analysis employs the AHP method with multiple parameters, including business age, business type, and business capital. According to research findings with applications, several BUMDES are declared unfit, while others are declared feasible. BUMDES with declared eligibility has AHP values ranging from 0.382 to 0.619. Meanwhile, BUMDES that are unworthy receives AHP values ranging from 0.235 to 0.239. It can also be determined based on the weight of each criterion as to whether or not it is appropriate for BUMDES. While the results of black box testing for the system's feasibility using 10 types of testing, including Equivalence Partitioning, Boundary Value Analysis/Limit Testing, Comparison Testing, Sample Testing, Robustness Testing, Behavior Testing, Performance Testing, Requirement Testing, Endurance Testing, and Cause-and-Effect Relationship Testing. Based on the test results, the system is 100% feasible to be used by users.